Investigation of the Stability of Methylammonium Lead Iodide (MAPbI(3)) Film Doped with Lead Cesium Triiodide (CsPbI(3)) Quantum Dots under an Oxygen Plasma Atmosphere - Huang, Pao-Hsun; Wang, Chi-Wei; Lien, Shui-Yang; Lee, Kuan-Wei; Wang, Na-Fu; Huang, Chien-Jung (MDPI, 2021)
In this study, we describe composited perovskite films based on the doping of lead cesium triiodide (CsPbI(3)) quantum dots (QDs) into methylammonium lead iodide (MAPbI(3)). CsPbI(3) QDs and MAPbI(3) were prepared by ligand-assisted re-precipitation and solution mixing, respectively. These films were optimized by oxygen plasma treatment, and the effect of powers from 0 to 80 W on the structural properties of the composited perovskite films is discussed. The experimental results showed that the light-harvesting ability of the films was enhanced at 20 W. The formation of the metastable state (lead(II) oxide and lead tetroxide) was demonstrated by peak differentiation-imitating. A low power enhanced the quality of the films due to the removal of organic impurities, whereas a high power caused surface damage in the films owing to the severe degradation of MAPbI(3).